First High-Angular Resolution L′ Images of the β Pictoris Debris Disc with the VLT / NaCo. Issue Volume 8:Issue S299(2013) (6th January 2014) - Milli, Julien; Mawet, Dimitri; Absil, Olivier; Lagrange, Anne-Marie; Mouillet, David; Girard, Julien H.; Augereau, Jean-Charles
Abstract: Imaging debris discs in the L ′-band (3.8 μm) is a difficult task. Quasi-static speckles from imperfect optics prevail below 1″ whereas background emission is the dominant noise source beyond that separation and is much larger than at shorter wavelengths. We demonstrate here the potential of the newly commissioned AGPM coronograph on VLT/NaCo combined with advanced star and sky subtraction technique based on Principal Component Analysis, and we analyze the morphology of the β Pictoris disc.